Transformation of Al-Ghazzali’s Thinking from Rational to Suphistic Trends - Zayyadi, Ahmad; Sofwan, Sofwan; Basit, Abdul (Future Science, 2022)
Talking about the transformation of Al-Ghazali's thought from rational to Sufistic tendencies is not as easy as al-Ghazali's changing the character of thought, but it requires a very long process. One of the indicators is that in 488 H. (1095 AD) al-Ghazali was in doubt, skeptical of the sciences he was studying. This skeptical state made al-Ghazali undergo quite drastic changes. Not a physical change, but/transformation of his thoughts, which at first tended to be rational and philosophical, in the end he chose the Sufi tendency as the character of his thinking. This article is of a library research nature and uses a historical approach to al-Ghazali's rational-sufistic epistemology with the theory of transformation in al-Ghazali's intellectual history from rational to sufistic in nature with a cross-disciplinary model, namely by combining rational and sufictic into one unified whole. , so that the hope is to emerge